Determinants of improved seed adoption and intensity in lentil farming: evidence from Terai region of Nepal - Damodar Gautam; Shiva Chandra Dhakal; Rishi Ram Kattel; Narayan Prasad Khanal (Cogent Food & Agriculture)
The prevailing dominance of the informal seed system and dramatically low seed replacement rate (SRR) are the potent evidence of poor adoption of improved lentil seed in Nepal. In this study, we used a logit model to identify the determinants of farmers’ decisions regarding the adoption of improved lentil seed in Nepal. A total of 300 participants, selected using stratified random sampling, were interviewed using a pretested questionnaire. Focus group discussions and key informant interviews were also conducted. The empirical results showed that owned land (p ≤ .047), number of economically active household members (p ≤ .018), improved seed knowledge (p ≤ .001), training (p ≤ .045), technical assistance (p ≤ .005), demonstration visits (p ≤ .001) and subsidies (p ≤ .035) had a significantly positive effect on the adoption of improved lentil seed, while waterlogging low land (p ≤ .049) and seed cost (p ≤ .032) had a significantly negative effect. The level of recommended technology adoption by improved seed adopters was calculated using the adoption index. The low adoption index (0.38) revealed the underutilization of recommended lentil production technologies by the improved seed adopters. The proportion of land with improved seed and the rate of seed used were satisfactory, but fertilizer and pesticide use were dramatically lower than the recommended level. To facilitate the sustainable adoption of improved seed, the government must place emphasis on holistic and robust research and extension services, technical assistance and demonstration visits, along with the implementation of targeted subsidy programs.